Indication of elective contralateral neck dissection in squamous cell carcinoma of the hypopharynx - Amar,Ali (2009)
Lymph node metastases (LNM) are common in hypophariyngeal carcinomas; the neck dissection is an important therapeutic approach. AIM: to analyze the incidence and distribution of LNM and failures in treating the contralateral neck. METHODS: a retrospective study of 174 patients with hypopharyngeal cancer treated from 1978 to 2003. The distribution of LNM and regional recurrences were evaluated. RESULTS: 44% of the cases were false negatives and 4.9% were false positives. Among the 48 patients who underwent bilateral ND, 29 had bilateral metastases and one had contralateral metastasis. Contralateral neck recurrences occurred in 12 cases that underwent unilateral ND. Among the nine patients with contralateral neck recurrence alone, eight were surgically salvaged. The risk of contralateral metastases was related to clinical staging (p=0.003) and involvement of the medial wall of the pyriform sinus (p=0.03), but not to radiotherapy (p=0.28). CONCLUSION: Contralateral metastases were more frequent when the medial wall of the pyriform sinus was affected, in the presence of ipsilateral palpable metastases and clinical stage IV.